An Integrated Approach for Screening and Identification of Positive Allosteric Modulators of N-Methyl-D-Aspartate Receptors. (June 2016) - Jambrina, Enrique; Cerne, Rok; Smith, Emery; Scampavia, Louis; Cuadrado, Maria; Findlay, Jeremy; Krambis, Michael J.; Wakulchik, Mark; Chase, Peter; Brunavs, Michael; Burris, Kevin D.; Gallagher, Peter; et al.
N-methyl-D-aspartate receptors (NMDARs) are ionotropic glutamate receptors that play an important role in synaptic plasticity and learning and memory formation. Malfunctioning of NMDARs, in particular the reduction in NMDAR activity, is thought to be implicated in major neurological disorders. NMDAR positive allosteric modulators (PAMs) represent potential therapeutic interventions for restoring normal NMDAR function. We report a novel screening approach for identification and characterization of NMDAR-PAMs. The approach combines high-throughput fluorescence imaging with automated electrophysiological recording of glutamate-evoked responses in HEK-293 cells expressing NR1/NR2A NMDAR subunits. Initial high-throughput screening (HTS) of a chemical library containing >810, 000 compounds using a calcium flux assay in 1536-well plate format identified a total of 864 NMDAR-PAMs. Concentration response determination in both calcium flux and automated electrophysiological assays found several novel chemical series with EC50 values between 0.49 and 10 µM. A small subset (six series) was selected and analyzed for pharmacological properties, subtype selectivity, mode of action, and activity at native NMDARs. Our approach demonstrates the successful application of HTS functional assays that led to identification of NMDAR-PAMs providing the foundation for further medicinal chemistry work that may lead to novel therapies for treatment of cognitive impairment associated with Alzheimer's disease and schizophrenia.